AI-DRIVEN OUTCOME-BASED EDUCATION: AN ADAPTIVE CURRICULUM DEVELOPMENT MODEL TO PRODUCE GLOBALLY COMPETITIVE GRADUATES IN THE SOCIETY 5.0 ERA - Farah Sajidatul Fathinah; Fathor Rachman (PROCEEDING OF INTERNATIONAL CONFERENCE ON EDUCATION, SOCIETY AND HUMANITY, 2026)
This study aims to develop a conceptual model of Artificial Intelligence driven Outcome Based Education (AI-Driven Adaptive OBE) as a strategy for curriculum transformation in higher education to produce graduates who are competent, adaptive, and globally competitive in the Society 5.0 era. The research employs a qualitative approach combining systematic literature review and design science research (DSR), synthesizing findings from fifteen peer-reviewed studies, institutional reports, and policy documents published between 2020 and 2025 on artificial intelligence in education, outcome-based education, and Society 5.0. Data were analyzed through thematic content analysis to identify recurring patterns in AI applications for curriculum design, learning outcome mapping, and labor market alignment. The findings reveal five interrelated components that should be integrated into an adaptive curriculum model: (1) AI based labor market competency needs analysis, (2) dynamic AI based mapping and evaluation of graduate learning outcomes (CPL), (3) a continuously updated adaptive curriculum mechanism, (4) AI based learning analytics as an academic decision support system, and (5) integration of global competencies such as AI literacy, digital literacy, sustainability awareness, and twenty first century soft skills. The proposed model repositions curriculum development from a static, periodic process into a continuous, data driven, and evidence based cycle in which human academic authority remains the final decision maker. The study concludes that AI-Driven Adaptive OBE offers a viable pathway for higher education institutions, particularly in Indonesia, to close the persistent gap between curriculum output and industry expectations, while safeguarding pedagogical quality and academic integrity.